Mathematics Education and Language - Brown, Tony. author. aut Link
IX, 270 p. 7 illus.
Keywords: `Contemporary thinking on philosophy and the social sciences has been dominated by analyses that emphasise the importance of language in understanding societies and individuals functioning within them; important developments which have been under-utilised by researchers in mathematics education. This book reaches out to contemporary work in these broader fields; drawing on original sources in key areas such as Gadamer and Ricoeur's development of hermeneutics, Habermas' work in critical social theory, Schutz's social phenomenology, Saussure's linguistics and the post-structuralist analysis of Derrida, Foucault and Barthes. Through examining the writings of these major thinkers it is shown how language is necessarily instrumental in developing mathematical understanding; but a language that is in a permanent state of becoming, resisting stable connections to the ideas it locates. The analysis offered extends from children doing mathematics to teachers inspecting and developing their own professional practices.'.